Efficacy Evaluation of Thymosin Alpha 1 in Non-severe Patients With COVID-19: A Retrospective Cohort Study Based on Propensity Score Matching - Huang, ChenLu; Fei, Ling; Xu, Wei; Li, WeiXia; Xie, XuDong; Li, Qiang; Chen, Liang (Frontiers in Medicine, 2021)
Objective Thymosin alpha 1 (Thymosin-α1) is a potential treatment for patients with COVID-19. We aimed to determine the effect of Thymosin-α1 in non-severe patients with COVID-19. Methods We retrospectively enrolled 1388 non-severe patients with COVID-19. The primary and secondary clinical outcomes were evaluated with comparisons between patients treated with or without Thymosin-α1 therapy. Results Among 1388 enrolled patients, 232 patients (16.7%) received both Thymosin-α1 therapy and standard therapy (Thymosin-α1 group), and 1156 patients (83.3%) received standard therapy (control group). After propensity score matching (1:1 ratio), baseline characteristics were well balanced between Thymosin-α1 group and control group. The proportion of patients progressed to severe COVID-19 is 2.17% for Thymosin-α1 group, and 2.71% for control group (p=0.736). The COVID-19-related mortality is 0.54% for Thymosin-α1 group, and 0 for control group (p=0.317). Compared with control group, Thymosin-α1 group had significantly shorter SARS-CoV-2 RNA shedding duration (13 vs 16 days, p=0.025) and hospital stay (14 vs 18 days, p＜0.001). No statistically significant difference was found between Thymosin-α1 group and control group in duration of symptoms (median, 4 vs 3 days, p=0.843) and antibiotic utilization rate (14.1% vs 15.2%, p=0.768). Conclusion For non-severe patients with COVID-19, Thymosin-α1 can shorten viral RNA shedding duration and hospital stay, but did not prevent COVID-19 progression and reduce COVID-19-related mortality rate.